Alginate- and Gelatin-Coated Apple Pieces as Carriers for Bifidobacterium animalis subsp. lactis DSM 10140 - Campaniello, Daniela; Bevilacqua, Antonio; Speranza, Barbara; Sinigaglia, Milena; Corbo, Maria Rosaria (Frontiers in Microbiology, 2020)
Fruit and vegetables are considered good natural supports for microorganisms; however, probiotics could cause negative changes on some organoleptic and sensory traits. Thus, the main topic of this paper was the design of coated-apple chips as carriers for probiotics with a high level of sensory traits. The research was divided into two steps. First, 4 functional strains (Limosilactobacillus reuteri DSM 20016, Bifidobacterium animalis subsp. lactis DSM 10140 and Lactiplantibacillus plantarum c16 and c19) were immobilized on apple pieces through dipping of fruit chips in probiotic suspensions for different contact times (from 15 to 30 min) and stored at 4°C for 12 days. Periodically, the viable count was assessed. As a result of this step, a contact time of 15 min was chosen because it assured an optimal deposition of microorganisms. In the second step, apple pieces inoculated with B. animalis subsp. lactis were coated with alginate and gelatin and stored at 4 and 8°C for 10 days; pH, microbiological counts, colour (browning index) and sensory scores were evaluated. B. animalis exerted a negative effect on apple chips and cause a significant browning; however, the use of coating counteracted this phenomenon. In fact, coated chips showed higher sensory scores and lower browning index. In addition, gelatin showed better perfomances in terms of probiotic viability, because at 8°C a significant viability loss of B. animalis (1.2 log cfu/g) was found on alginate-coated chips. Gelatin-coated apple pieces with B. animalis subsp. lactis could be an attractive functional food for a wide audience, although further investigations are required on in vivo effects of this product after the consumption.